Diabetes and the Brain - Biessels, Geert Jan.; Luchsinger, Jose A.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Diabetes, particularly type 2, has become increasingly more common around the world. Consequently, the effect of diabetes on the brain has achieved enormous public health importance. A surge in pre-clinical and clinical research on topics ranging from management of hyperglycemia in acute stroke to disturbances in insulin signaling in Alzheimer's disease has led to substantial progress in the field. Written by a panel of international experts, Diabetes and the Brain provides in depth reviews on the cerebral complications of diabetes, and offers introductory chapters on current insights on the pathophysiology and clinical management of diabetes, as well as neuropsychological assessment and dementia. This relevant and easily accessible book explains the cerebral complications of diabetes, with an update on diabetes for neurologists, psychiatrists, and mental health providers and researchers in general,and on stroke and dementia for those involved in research and clinical practice in diabetes.
Update on Diabetes for Neurologists -- Type 1 Diabetes -- Type 2 Diabetes -- Update on Stroke and Dementia for Diabetologists -- Acute Ischemic Stroke -- Neuropsychological Assessment -- Clinical Evaluation and Treatment of Cognitive Dysfunction and Dementia -- Acute Cerebral Disturbances in Diabetes -- Hypoglycemia -- Ketoacidosis and Hyperglycemic Hyperosmolar State -- Stroke and Diabetes Mellitus -- Hyperglycemia in Acute Stroke -- Long-Term Cerebral Complications in Diabetes -- Cognition in Children and Adolescents with Type 1 Diabetes -- Cognition in Adults with Type 1 Diabetes -- Cognition in Type 2 Diabetes or Pre-diabetic Stages -- Type 2 Diabetes, Related Conditions, and Dementia -- Diabetes and Depression -- Central Nervous System Involvement in Diabetic Neuropathy -- Experimental Models and Pathophysiology -- Animal Models -- Pathobiology of Diabetic Encephalopathy in Animal Models -- The Role of Insulin Resistance in Age-Related Cognitive Decline and Dementia.
Keywords: Medicine; Internal medicine; Angiography; Endocrinology; Neurology; Medicine & Public Health; Endocrinology; Neurology; Angiology; Internal Medicine